Sistem Operasional Manajemen Dalam Pengelolaan Cafe Selasa Communa Di Era Generasi Z - Alfin Agung Azhar; Nabilah Salsabilah; Junnanda, Junnanda; Zainarti, Zainarti (Pusat Riset dan Inovasi Nasional, 2022)
In this generation Z era, business actors are starting to have a lot of interest in the culinary realm, one of which is the contemporary café which is conceptualized in such a way as to be attractive and right at the target market. The main target market for these business actors is teenagers to adults, but the café concept is made in such a way that it can also be enjoyed by those who want to bring their families. In building a business we have to prepare various things, especially the operational system and business management. A good operational and management system can determine the success and effectiveness of the company's work.